Upgrading of Canadian Oil Sand Bitumen via Cracking and Coke Gasification: Effect of Catalyst and Operating Parameters - Zhang, Y.; Huang, L.; Zhang, X.; Sun, G.; Gao, S.; Zhang, Shu (American Chemical Society, 2017)
© 2017 American Chemical Society. Canadian oil sand bitumen was stepwise converted via an integrated cracking and coke gasification (ICCG) process. The cracking behaviors of oil sand bitumen were investigated in a fluidized bed reactor with FCC and bifunctional (BFC) catalysts, respectively. The BFC catalyst specialized for the ICCG process was designed with both cracking and gasification activities. The results showed that the liquid yield of 78 wt % and conversion ratio of 87% of oil cracking could be simultaneously realized over hydrothermally treated catalysts (A-FCC and A-BFC) at 510 °C. The cracking performance of catalysts was closely related with their acidity, as indicated by NH 3 -TPD analysis. Coke deposit on the catalyst could lead to severe pore blockage. Catalyst regeneration via coke gasification could recover its pore structures and meanwhile produce high-quality syngas with the sum of H 2 and CO up to 80 vol %. Comparing with FCC catalysts, the regeneration (coke gasification) time over BFC catalysts was shortened by about 30% due to its well-developed pores and high alkaline oxides content, and these effects could be further enhanced by impregnating potassium oxides as catalytic additives. Finally, the alternating cracking-gasification operation was conducted for four cycles to justify the stability of BFC catalyst. The newly designed amorphous BFC catalyst exhibited high hydrothermal stability and could be potentially used for oil sand bitumen upgrading via the ICCG process in a large scale.